Endovascular treatment options in central venous stenosis and occlusion: Angioplasty or Stent ? - Behlül İgüs; Ali Fırat; Hüseyin Yüce Bircan (Ankara Medical Journal, 2020)
INTRODUCTION: The purpose of this study was to compare the patency rate outcomes and efficacy of percutaneous transluminal angioplasty (PTA) versus percutaneous transluminal stenting (PTS) for the treatment of central vein stenosis and occlusion in hemodialysis patients. METHODS: A total of 71 chronic hemodialysis patients (36 males, 35 females) with 142 events of central venous stenosis or occlusion underwent 109 endovascular interventions between March 2013 and June 2018. The clinical follow-up of the patients was performed with control venography at 1, 3, and 6 months, and then at 6-month intervals for asymptomatic patients. RESULTS: PTA was applied to 45 patients and PTS to 26 patients during the study period. At 3, 6,12 and 24 months, primary patency rates were 97.74%, 88.23%, 73.76% and 50.76% respectively in the PTA group and 96.23%, 92.34%, 65.96% and 47% in the PTS group. Assisted primary patency at 3, 6, and 12 months was 97.73%, 90.76%, and 75.92% respectively in the PTA group and 96.25%, 84.38%, and 79.87% in the PTS group. No statistically significant difference was determined between the groups in respect of primary and assisted patency rates (p=0.216, p=0.121). The average number of interventions in the PTS group (2.62+- 1.23) was significantly higher than that in the PTA group (1.43+-0.62). DISCUSSION AND CONCLUSION: Endovascular treatment is a safe and effective method in the management of central vein occlusion. PTS does not result in longer patency in the treatment, but conversely incurs greater costs and necessitates more interventions to provide patency. Therefore, PTS should only be preferred for PTA-resistant lesions or concurrent lesions.